2006
DOI: 10.1111/j.1439-0396.2005.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Late development of homoeothermy in mink (Mustela vison) kits – a strategy for maximum survival rate*

Abstract: The objective of this study was to establish the age at which mink kits develop functional homoeothermy. The investigation was based on the hypothesis that in this species with very immature neonates, late development of homoeothermy may be an adaptation to economize with energy. Measurements of heat production (HE) by means of indirect calorimetry lasting 3 h were performed on neonatal kits and kits from 1 to 54 days of age. Both single kits and groups of 4-5 huddling kits were kept at 15 degrees C (L) or 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Young mink are unable to maintain the proper body temperature up to 22-29 days after birth (Harjunpää and Rouvinen-Watt, 2004). The huddling effect can last up to 14 days or even up to 30 days after birth depending on many factors, e.g., environmental conditions, litter size, access to feed (Tauson et al, 2006). Only after that time, kits open their eyes (Brandt et al, 2013) and start to separate themselves from the siblings in the same nest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young mink are unable to maintain the proper body temperature up to 22-29 days after birth (Harjunpää and Rouvinen-Watt, 2004). The huddling effect can last up to 14 days or even up to 30 days after birth depending on many factors, e.g., environmental conditions, litter size, access to feed (Tauson et al, 2006). Only after that time, kits open their eyes (Brandt et al, 2013) and start to separate themselves from the siblings in the same nest.…”
Section: Discussionmentioning
confidence: 99%
“…The care of offspring after the birth and the lactation period play an important role in the life of young mink as these factors affect offspring growth and development (Newberry and Swanson, 2008). The survival of young animals directly depends on the involvement of the dams in care as well as environmental conditions (temperature, design) prevailing in the nest (Tauson et al, 2006;Malmkvist et al, 2007;Zschille et al, 2010). The time the female spends for the care of the young is important not only from ABSTRACT.…”
Section: Introductionmentioning
confidence: 99%
“…However, larger space and low density of animals might result in increased use of energy for maintaining sufficient body temperature compared with those mink that were kept in single-storey cages, where animals remained in close contact. According to Tauson et al (2006), mink kept in groups, that is, in higher density, accumulated less subcutaneous fat than those kept in pairs, since they did not need to use so much energy to maintain proper body temperature. The in-house research indicated only slight differences in bodyweight gains.…”
Section: Discussionmentioning
confidence: 99%
“…The closer huddling we observed at higher ambient temperatures could be a function of swifts trying to reduce evaporative water loss. At higher temperatures, the use of sheltered roosts (Bakken et al 1991) and huddling have been observed to reduce evaporative water loss in many taxa (Tauson et al 2006, Boratynski et al 2015. However, we did not measure water balances in swifts and this remains an area worth exploring in further study.…”
Section: Periodmentioning
confidence: 94%